Potential hepato-protective effect of Salvia hispanica (chia) and Chenopodium quinoa (quinoa) in diabetic male albino rats - Eshraa, Maha; El Sahn, Fikrat; Aborhyem, Samar (International Journal of Public Health Science (IJPHS), 2024)
Chia and quinoa seeds are novel sources of bioactive compounds that may improve lipid profile, blood glucose homeostasis, and body weight in diabetic rats. This work aims to study the effect of different percentages of chia and quinoa consumption, alone or in a mixture, compared to Metformin drug on regulating lipid profile, blood glucose level, and weight of male diabetic rats. The consumption of quinoa and chia seeds showed a significant decline in fasting blood glucose (FBG), fasting insulin level, Hemoglobin A1C (HbA1c), and Homeostatic Model Assessment for Insulin (HOMA-IR), while the best results were obtained with Metformin and chia seeds. A decrease in mean body weight, triglycerides, total cholesterol, low density lipoprotein (LDL-C), and very low-density lipoprotein (VLDL-C), and an increase in high density lipoprotein (HDL-C) occurred, which was significant when consuming chia and quinoa seeds rather than treatment with metformin. Chia and quinoa seeds could improve blood glucose homeostasis and lipid profile in diabetic rats. These research findings could promote the daily consumption of quinoa and chia as great functional foods that could improve blood glucose homeostasis and lipid profile.